Designing future cities for wellbeing - Boyko, Christopher; Cooper, Rachel 1953-; Dunn, Nick 1974- (Routledge, 2020)
"Designing Future Cities for Wellbeing draws on original research bringing together dimensions of cities we know have a bearing on our health and wellbeing--including transportation, housing, energy, and foodways--and illustrates the role of design in delivering cities in the future that can enhance our health and wellbeing. It aims to demonstrate that cities are a complex interplay of these various dimensions that both shape, and are shaped by, existing and emerging city structures, governance, design and planning. Explaining how to consider these interconnecting dimensions in the way in which professionals and citizens think about and design the city for future generations' health and wellbeing, therefore, is key. The chapters draw on UK case and research examples and make comparison to international cities and examples. This book will be of great interest to researchers and students in planning, public policy, public health, and design"--
Description based upon online resource; title from PDF title page (viewed October 5, 2020)
Keywords: City planning / Environmental aspects; Cities and towns / Technological innovations; Political planning; Public health